Aspectos morais e religiosos da ação política, em Maquiavel - Amorim, Edson Luis de (2010)
The dissertation MORAL AND RELIGIOUS ASPECTS OF THE POLITICAL ACTION IN MACHIAVELLI, presents Machiavelli as an author who worked on deepening the political action in the early 1600 s, when the Renaissance humanist culture reached its peak, witnessing an Italy affected by a political, moral and religious crisis. The history of Italy and of the North Republics, especially Florence, Machiavelli s birthplace, is the basis for this research, seeking to understand some aspects of his way of thinking which helped his ideas about the moral sphere with the political one and the political character of religion and human nature, especially in Discorsi and The Prince. The political game that unfolds in the Machiavellian thought takes place essentially in the undetermined land of human actions, in which the good and the evil are easily needed in these actions, but only the actions that are harmful and the ones that corroborate to the maintenance of liberty interest him most. This research aims at showing that even though he was not a moralist, he was able to establish fundamental principles of human conduct in a philosophical sense, when he analyzed the aspect of the political techné, being able to launch a new and different view in the search for what is possible, effective, in a universe of possibilities for those who seek to be successful in their actions. He noticed that the classical ethical discourse, of the absolute norms, could not explain human action, especially in the political sphere. In the religious aspect, the Florentine praises the Roman potency through their uses [constituioni] and sacrifice rituals, acts and shows the reasons for their greatness by being strong combating with energy, showing which the ancient people depended on to be advocates of freedom and tolerance. He confirms that religion may allow for exaltation and defense of a country, it wants us to love and honor, so everybody must be well prepared, that is to say, educated in the love for liberty, as many republics in ancient times, always ready to defend it. Thus, In Machiavelli, religion has a double meaning: it is an instrumentum regni , the means by which, in the name of God, an accorded legislator can lead the great, and also an extraordinary enterprise. Nevertheless, facing excessive ambition and corruption, the solution to keep the civil order in the corrupted republic suggested by the Florentine is noble hands